Pengaruh Healing Touch Terhadap Kecemasan Pada Pasien Infarak Miokard Di Rsud Syarifah Ambami Rato Ebu Bangakalan - Mufarika M.Kep (NHM PRESS, 2019)
Acute myocardial infarction is a type of coronary heart disease that has a prevalence in Indonesia in 2013 of 0.5% or an estimated 883,447 people. Anxiety may be a risk factor for a poorer prognosis and an increased risk of death in patients with acute myocardial infarction. The results of preliminary study concluded that as many as 60% of respondents have a severe anxiety. The purpose of this study was to determine the effect of healing touch on anxiety in patients with Acute Myocardial Infarction at Syarifah Ambami Rato Ebu Bangkalan Hospital. The design of this study was pre-experimental and the design used one group pretest post test with anxiety variables on acute myocardial infarction and healing touch. The population of the study were 11 respondents and the samples taken were 11 respondents in Irna B Syarifah Ambami Rato Ebu Bangkalan Hospital. Sampling technique using purposive sampling. While the data collection tool using observation checklist sheet with test statistical test Wilcoxon Match Pairs Test. Result showed that there was a difference of decrease in anxiety before and after given healing touch. Wilcoxon Match Pairs Test results obtained results P Value 0,020, which means H0 rejected means there is influence of healing touch on anxiety in patients with Acute Myocardial Infarction in RSUD Syarifah Ambami Rato Ebu Bangkalan. From the results showed that healing touch can reduce anxiety in patients with Acute Myocardial Infarction so that researchers expect for other researchers to develop the number of samples become larger so that the results of the study can be more generalized.